Measurement of Educational Feasibility Using Cost and Benefit Analysis at STAINU Temanggung - Sutarman Sutarman; Yuni Setya Hartati; Puteri Anggita Dewi (Universitas Muhammadiyah Mataram, 2020)
Current social reality produces a conclusion that the purpose of education is inseparable from employment. Therefore, the feasibility of Indonesian education needs to be considered in terms of the benefits obtained by its graduates. Management Discipline has a formula regarding profit and loss. This formula can be adopted in education management. Furthermore, in this study this formula is referred to as a cost and benefit analysis. Adoption of this formula requires a reinterpretation of all the components in it. Net benefit (NB) is the result of reduction and direct benefit and indirect benefits with costs (C) and depreciation (D). This research uses research and development methods Data collection was carried out by interview method and questionnaire. Sampling is carried out by random sampling technique The results of this calculation are then consulted with the range that has been made in the form of a percentage. The trial conducted on the feasibility of education at STAINU Temanggung University showed that the educational feasibility level at the faculty was 29.72%. This means that the university has an enough feasible meaning in implementing education if analyzed from a cost and benefit analysis